Encapsulation of anthocyanin with gelatin-alginate carrier by a specially designed ultrasonic encapsulator with adjustable frequency - Sarıoğlu, Kemal; Ülgen, Ahmet; Oral, Rasim Alper (John Wiley and Sons Inc, 2024)
Anthocyanins are of increasing interest for food applications due to their health benefits. However, their poor stability and susceptibility to unfavorable environmental conditions may limit their application. Microencapsulation offers enhanced stability and controlled release properties. The aim was designing an ultrasonic encapsulator with a variable frequency ultrasonic driver to encapsulate black carrot and mahaleb anthocyanins. First, a double-channel variable frequency and power adjustable ultrasonic driver and atomizer head were designed. The cooled gelation technique was used to encapsulate anthocyanin in an alginate-gelatin complex. Freeze-drying and air-drying techniques were used for drying of microcapsules. Encapsulation parameters were atomization frequency, alginate, and anthocyanin concentrations. The capsules were characterized by encapsulation efficiency, particle diameter, and controlled release rates. Controlled release tests were performed at two different temperatures and pH values. Encapsulation efficiency was 87%–95%, mean diameters were between 69 and 95 ?m. Maximum release rates were obtained from freeze-dried mahaleb anthocyanin capsules. Release rates increased with increasing temperature and pH values. In addition, the experimental results showed that the increase in the amount of alginate used in encapsulation decreased the release rate. Moreover, the results proved that the designed encapsulator can be used for encapsulation in fields such as food, pharmaceuticals, polymers, chemistry, and materials. © 2023 Wiley Periodicals LLC.
Keywords: anthocyanin; black carrot; encapsulation; frequency; mahaleb; ultrasonic atomizer